Orchestra of ligand-activated transcription factors in the molecular symphony of SERPINE 1 / PAI-1 gene regulation - Vrzalova, Aneta; Vrzal, Radim (Biochimie, 2025)
Plasminogen activator inhibitor 1 (PAI-1) is a crucial serine protease inhibitor that prevents plasminogen activation by inhibiting tissue- and urokinase-type plasminogen activators (tPA, uPA). PAI-1 is well-known for its role in modulating hemocoagulation or extracellular matrix formation by inhibiting plasmin or matrix metalloproteinases, respectively. PAI-1 is induced by pro-inflammatory cytokines across various tissues, yet its regulation by ligand-activated transcription factors is partly disregarded. Therefore, we have attempted to summarize the current knowledge on the transcriptional regulation of PAI-1 expression by the most relevant xenobiotic and endocrine receptors implicated in modulating PAI-1 levels. This review aims to contribute to the understanding of the specific, often tissue-dependent regulation of PAI-1 and provide insights into the modulation of PAI-1 levels beyond its direct inhibition.
Keywords: Gene Expression Regulation; Ligands; inhibitor aktivátoru plazminogenu 1; Animals; lidé; Plasminogen Activator Inhibitor 1; Transcription Factors; ligandy; transkripční faktory; Humans; zvířata; regulace genové exprese